Comparison of Vaginal Versus Sublingual Misoprostol in the Treatment of First-Trimester Missed Miscarriages - Qadir, Maimoona (Journal of Gandhara Medical and Dental Science, 2024)
OBJECTIVES To evaluate the efficacy of sublingual versus vaginal misoprostol for the treatment of missed miscarriages in the first trimester of pregnancy. METHODOLOGY The gynecology and obstetrics department of Khyber Teaching Hospital in Peshawar conducted this Randomized Controlled Trial investigation from January 2021 to December 2023. Two groups of patients were formed, according to the FIGO procedure, based on whether misoprostol was given vaginally or orally. The dosages of 800 micrograms were administered vaginally to the first group and sublingually to the second group every three hours. Patients were observed for vaginal bleeding and evacuation after 24 hours; if neither happened, the dose was repeated. RESULTS The groups did not differ statistically (P-value > 0.05). The mean age of the patients (26.56 ± 5.73 versus 25.45 ± 5.63), parity of the patients (3.31 ± 0.56 versus 3.22 ± 0.54), period of gestation (8.85 ± 1.63 versus 9.37 ± 1.48), and time from initiation of induction till expulsion (13.68 ± 3.52 versus 12.94 ± 3.45) were similar in both groups. For a complete miscarriage in the vaginal misoprostol group, more doses (4.28 ± 0.65 vs 3.26 ± 1.23, P-value < 0.05) were needed. In comparison to the vaginal misoprostol group (56%), the sublingual group (91.6%) reported feeling more comfortable (P-value < 0.05) throughout the drug’s administration. The sublingual misoprostol group had a considerably (P-value < 0.05) better success rate (77.66%) compared to the vaginal misoprostol group (56.32%). Such adverse effects as bleeding during menstruation (68.33% versus 93.33%), vaginal bleeding (31.66% versus 84%), and diarrhoea (30.57% vs 59%) had significant (P-value < 0.05) association with sublingual misoprostol. CONCLUSION The efficacy of sublingual misoprostol surpasses vaginal misoprostol. Patients are more satisfied and respond more favourably to the sublingual approach.